Evaluation of awareness of mold infections in stored maize (Zea mays L.) and groundnut (Arachis hypogaea L.) in Anseba, Debub and Maekel Regions (Zoba) of Eritrea - Oliver O. Okumu; Rao Sethumadhava; Even Z. Melika; Teklemariam M. Divora; P. G. Samuel; Brhane F. Even; Said J. Yasmin; Tsegay T. Abel (Innovations in Agriculture)
Survey on farmers’ awareness of mould infection in maize and groundnuts were conducted in various villages in Anseba, Debub and Maekel regions of Eritrea during the summer period between July and December 2023. We administered questionnaires to various farmers in the study areas to assess their knowledge and awareness of mold infections during storage. Maize and groundnut samples were collected for further analysis in the laboratory. It was observed that majority of the farmers had limited knowledge about the timing of infection, contamination, and risks associated with molds. However, more than half (57%) of the respondents were able to identify spoilt grains through rotting (48%), visible insects (21%), and discolouration (10%). The respondents reported several uses for infected grains: approximately 34% consumed them, 26% fed them to livestock and 18.4% sold them to unsuspecting customers. None of the interviewed farmers were aware of the term “mycotoxins” or the associated health hazards while 67% of the respondents did not know measures for controlling mould fungal infection. There was a positive correlation (p ≤ 0.001, r = 0.804) between farmers’ knowledge of mold fungi and their ability to understand mycotoxin contamination. Laboratory analysis revealed the presence of Aspergillus niger, A. flavus, A. parasiticus, Fusarium verticillioides and Penicillium spp. Grains from Koffo storage structure had the highest incidence of mold infection in comparison with other traditional storage structures. These findings indicate a general lack of knowledge about mold fungal infections and the risks among the respondents. Thus, the findings underscore the need for tailored interventions through the ministry of agriculture to promote good agricultural practices aimed at reducing mold and mycotoxin contaminations.